Rehabilitation of a missing ear with an implant retained auricular prosthesis - Satyabodh Sheshraj Guttal; Shruti Shanbhag; Sudhindra S Kulkarni; Srinath L Thakur (Wolters Kluwer Medknow Publications, 2015)
Burns can leave a patient with a severely debilitating disability even after treatment. The objectives of burn rehabilitation are to minimize the adverse effects caused by the injury while rehabilitating the patient's physical and psychological well-being, maximizing social integration. Long-term success of maxillofacial prostheses mainly depends on the retention. Extra oral implant retained prostheses have proved to be a predictable treatment option for maxillofacial rehabilitation. Replacement of a severely deformed external ear with burned tissues may be satisfactorily accomplished by a cosmetic prosthesis anchored by implants integrated in the skull. The use of such implants is now a well-recognized method for creating a stable result in maxillofacial rehabilitation. This case report describes a safe, simple and economical method for the rehabilitation of a patient with missing right auricle using an implant supported silicone prosthesis. The implant was placed in the mastoid region of the temporal bone. Reconstruction of the ear was done with auricular silicone prosthesis, retained using magnets incorporated in an autopolymerizing resin shim to decrease the weight of the prosthesis on a single implant. This method eliminates the need of tedious laboratory procedures and exact casting and fitting requirements of a metal substructure while minimizing the overall weight and cost of the prosthesis while maintaining adequate support, esthetics and retention of the prosthesis.